Implementasi Program Turjuman Al-Qur’an dalam Membentuk Akhlak Kepada Allah Swt pada Kelompok Akhwat di SMP IT Anni’mah Bandung - Resty Hadianingtyas; Asikin, Ikin; Nur Inten, Dinar (UNISBA Press, 2024)
Abstract. The most important character that must be taught to someone is character to Allah Swt. The Turjuman Al-Qur'an program is a Qur'anic learning that can be used to make it easier for students to understand the meaning of each word, each sentence and the essence of the Qur'anic verse. This research aims to: (1) to know the planning of the Al-Qur'an turjuman program in shaping morals to Allah Swt in the akhwat group, (2) to know the implementation of the Al-Qur'an turjuman program in shaping morals to Allah Swt in the akhwat group, (3) to know the evaluation of the Al-Qur'an turjuman program in shaping morals to Allah Swt in the akhwat group, (4) to know the obstacles and solutions to the Al-Qur'an turjuman program in shaping morals to Allah SWT in the akhwat group at SMP IT Anni'mah Bandung. The results showed that: (1) The planning of the Turjuman Al-Qur'an program is carried out in a comprehensive and structured manner to ensure that students understand and practice the teachings of the Qur'an in their daily lives. (2) The implementation of the Turjuman Al-Qur'an program in shaping morals to Allah SWT in the akhwat group, has three parts, namely: opening, core activities, and closing. (3) Evaluation in this program is carried out through end of lesson assessments, observation of students' daily behavior, and the use of questionnaires and surveys (4) Obstacles and solutions in the Qur'anic turjuman program; obstacles: including time constraints due to busy academic schedules, and lack of support from some parents. Solutions: adjustments to the learning schedule and increased communication with parents. Abstrak. Akhlak paling utama yang harus diajarkan kepada seseorang adalah akhlak kepada Allah Swt. Program Turjuman Al-Qur’an adalah suatu pembelajaran Al-Qur’an yang dapat digunakan untuk memudahkan siswa dalam memahami makna perkata, perkalimat serta intisari dari ayat Al-Qur’an. Peneliti ini bertujuan untuk: (1) mengetahui perencanaan program turjuman Al-Qur’an dalam membentuk akhlak kepada Allah Swt pada kelompok akhwat, (2) mengetahui pelaksanaan program turjuman Al-Qur’an dalam membentuk akhlak kepada Allah Swt pada kelompok akhwat, (3) mengetahui evaluasi program turjuman Al-Qur’an dalam membentuk akhlak kepada Allah Swt pada kelompok akhwat, (4) mengetahui hambatan dan solusi program turjuman Al-Qur’an dalam membentuk akhlak kepada Allah Swt pada kelompok akhwat di SMP IT Anni’mah Bandung. Hasil penelitian menunjukkan bahwasanya: (1) Perencanaan program Turjuman Al-Qur'an dilakukan secara komprehensif dan terstruktur untuk memastikan siswa memahami dan mengamalkan ajaran Al-Qur'an dalam kehidupan sehari-hari. (2) Pelaksanaan program turjuman Al-Qur’an dalam membentuk akhlak kepada Allah Swt pada kelompok akhwat, memiliki tiga bagian, yaitu: pembukaan, kegiatan inti, dan penutup. (3) Evaluasi dalam program ini dilakukan melalui penilaian akhir pelajaran, observasi perilaku sehari-hari siswa, dan penggunaan kuesioner serta survei (4) Hambatan dan solusi dalam program ini; hambatan: termasuk keterbatasan waktu akibat jadwal akademik yang padat, dan kurangnya dukungan dari sebagian orang tua. Solusi: penyesuaian jadwal pembelajaran dan peningkatan komunikasi dengan orang tua.